Pengembangan Modul Inventori Pada Supply Chain Management PT Sampoerna Pagi - Muhammad Hafidz Novriantama; Herman Tolle; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
PT Sampoerna Pagi is a building materials company that is experienced in the field of building materials that guarantee the price and quality of the materials provided. In the direction of the company towards large and complex developments, the needs for information systems and its management that is not integrated becomes an obstacle for the company to progress. The company does not have an information system that facilitates the management of purchasing materials from suppliers, shipping materials from warehouse to stores, to fellow stores, and the history of materials availability in the warehouse. In addition, the Enterprise Resource Planning (ERP) modules that have not been integrated cause the company to still manage data manually. Thus, the company needs new supply chain management (SCM) modules that are integrated by existing systems in the company's ERP. As a result, the company's activities become longer and prone to mistakes, so the company's activities become ineffective and inefficient, and affect the company's profits. Therefore, we need an Electronic Supply Chain Management (e-SCM) module that is integrated with other ERP modules. To overcome these problems, the author builds a supply chain management system using prototyping methods and laravel framework. The research results obtained a usability score of 72.5. The score is included in the predicate B- which means the score is interpreted as an above average score. Therefore, the system is categorized as a system that is easy to use and well-received by users.